Cytotoxic aromatic polyketides from an insect derived Streptomyces sp. NA4286. Issue 26 (27th June 2019) - Cheng, Ping; Xu, Kuang; Chen, Yan Chi; Wang, Ting Ting; Chen, Yu; Yang, Cheng Long; Ma, Shi Ying; Liang, Yong; Ge, Hui Ming; Jiao, Rui Hua
Graphical abstract: Highlights: Murayaquinones B-E (1 –4 ) were isolated from an insect derived actinobacterium. Structures of new compounds were elucidated by analysis their spectroscopic data. Murayaquinone D exhibited cytotoxic activities against six cancer cell lines. Abstract: Chemical study of the insect-derived bacterium, Streptomyces sp. NA4286, led to the discovery of four new polyketides, murayaquinones B-E (1 –4 ), together with a known compound, murayaquinone (5 ). The structures of new compounds (1 –4 ) were determined by extensive analysis of their NMR and HRESIMS data. The absolute configuration of (+)-1 and (−)-1 was assigned through comparison of experimental and calculated ECD spectra. Murayaquinone D (3 ) exhibited potent cytotoxic activities against six human cancer cell lines with IC50 values ranging from 1.03 to 9.99 μM.